2018
DOI: 10.5433/1679-0359.2018v39n2p711
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exogenous enzymes on the performance and digestibility of nutrients in broiler

Abstract: Here we tested how feeding with exogenous enzymes affects the performance, carcass yield, and ileal digestibility in broilers from 21-to 42-days-old. The study included 1008 male broilers randomly distributed into six diets: positive control (PC), corn and soybean meal containing all the nutritional requirements; negative control (NC), with a 120 kcal.kg -1 reduction in metabolizable energy relative to the PC; enzyme complex one (NC + 100 ppm of endo-1,4-beta-xylanase); enzyme complex two (NC + 200 ppm of xyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It is reported that exogenous enzyme supplemented in diets can improve nutrition levels and utilization of feed, enhance secretion and activity of the endogenous digestive enzyme, overcome the anti-nutrition factors in feed and reduce the pollution of animals to the environment and improve the performance of animals (Cain & Garling, 1995;Carvalho et al, 2017;Jendza, Dilger, Adedokun, Sands, & Adeola, 2005;Ravindran & Son, 2011). It has been demonstrated that the effectiveness in many animals, such as broiler chickens (Alefzadeh et al, 2016;Andrade, Nunes, Wachholz, Da Silva, & de Freitas, 2018;Kutlu et al, 2019), cows (Gencoglu et al, 2010;Vahora & Pande, 2006), sheeps (Lopez-Aguirre et al, 2016;Salem et al, 2012), growing and weaned pigs (Garry, Fogarty, Curran, & O'Doherty, 2007;Torres-Pitarch et al, 2017;Wang, Xu, Sun, & Kim, 2008), needs more researches to explore the mechanism of exogenous enzyme supplemented in diets about aquatic animals. Japanese seabass, Lateolabrax japonicus is one of the most popular aquaculture species in China, which has been widely cultured because of its fast-growing, adaptable and high-quality meat.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that exogenous enzyme supplemented in diets can improve nutrition levels and utilization of feed, enhance secretion and activity of the endogenous digestive enzyme, overcome the anti-nutrition factors in feed and reduce the pollution of animals to the environment and improve the performance of animals (Cain & Garling, 1995;Carvalho et al, 2017;Jendza, Dilger, Adedokun, Sands, & Adeola, 2005;Ravindran & Son, 2011). It has been demonstrated that the effectiveness in many animals, such as broiler chickens (Alefzadeh et al, 2016;Andrade, Nunes, Wachholz, Da Silva, & de Freitas, 2018;Kutlu et al, 2019), cows (Gencoglu et al, 2010;Vahora & Pande, 2006), sheeps (Lopez-Aguirre et al, 2016;Salem et al, 2012), growing and weaned pigs (Garry, Fogarty, Curran, & O'Doherty, 2007;Torres-Pitarch et al, 2017;Wang, Xu, Sun, & Kim, 2008), needs more researches to explore the mechanism of exogenous enzyme supplemented in diets about aquatic animals. Japanese seabass, Lateolabrax japonicus is one of the most popular aquaculture species in China, which has been widely cultured because of its fast-growing, adaptable and high-quality meat.…”
Section: Introductionmentioning
confidence: 99%